Going to Boston : Harriet Robinson's Journey to New Womanhood - Robinson, Harriet Jane Hanson, 1825-1911 (Book collections on Project MUSE., 2017)
"One nineteenth-century woman's journey in a changing Boston: As a poet, author, and keen observer of life in 1870s Boston, Harriet Robinson played an essential--if occasionally underappreciated--role in the women's suffrage movement during Boston's golden age. Robinson flourished after leaving behind her humble roots in the mill town of Lowell, Massachusetts, deciding to spend a year in Boston discovering the culture and politics of America's Athens. An honest, bright, and perceptive witness, she meets with Emerson and Julia Ward Howe, with whom she organizes the New England Women's Club, and drinks deeply of the city's artistic and cultural offerings. Noted historian Claudia L. Bushman proves a wonderful guide as she weaves together Robinson's journal entries, her own learned commentary, and selections from other nineteenth-century writers to reveal the impact of the Industrial Revolution and the rise of women's suffrage as seen through the experience of one articulate, engaged participant. Going to Boston will appeal to readers interested in both the history of Boston and the history of American progress itself; 'With observations as astute and as lively as those of her subject, Claudia Bushman shows us how Harriet Robinson, former mill-girl and aspiring middle-class housewife, became an activist for women's rights. Interspersing her own interpretations with vibrant selections from Robinson's diary, Bushman demonstrates that engagement in the cause was transformative even though the ultimate goal--votes for women--remained elusive'--Laurel Thatcher Ulrich, Harvard University; 'A sharp-eyed woman steps out of this book, a woman who filled her journal with vignettes of everyone from Emerson and aging abolitionists to up-and-coming reformers agitating for women's rights. A writer and reformer herself, Harriet Robinson becomes an insightful guide to Boston in 1870 ... A gem of a book'--David D. Hall, Harvard University; 'A richly rewarding encounter with a conventional middle-class wife and mother in the postbellum period as she gains a growing devotion to the cause of women's suffrage. You'll feel almost as though she were a personal friend'--Armand L. Mauss, Washington State University"--Publisher description.